Perdidas por sustracción o consumo de productos en Autoservicio Anthony de la avenida universitaria de Babahoyo año 2022. - Gutiérrez Diaz, Erick Andrés (2023)
The present case study is oriented to demonstrate what losses are recorded by theft or consumption of products inside the Anthony self-service store on Avenida Universidad de Babahoyo in 2022, considering that these losses occur in different ways and in all commercials, indicating that it is impossible to eliminate them but if they can be controlled, due to their size and control they rarely affect the finances or the economy of the commercials, however their constancy must be observed, analyzed and controlled to maintain their rates, in this case study a design is applied descriptive that has a qualitative, cross-sectional approach insofar as a phenomenon is studied in a certain time, it uses inductive-deductive and analytical-synthetic methods that carefully investigate, expose and summarize the information and then carefully analyze the results, it has the documentary modality to collect theoretical and field information when applying the techniques data collection, which in this case is the interview by means of a questionnaire that is applied to the owner of the establishment and an employee of the same, obtaining as results, in the self-service Anthony if there are losses for different reasons or reasons, these losses will from theft or theft of products, either by customers or people of dubious origin, customers or users, "zero loss" or "zero loss" is impossible to obtain as a result, but its impact can be controlled.